Safety and efficacy of venom immunotherapy: a real life study - Kołaczek, Agnieszka; Skorupa, Dawid; Antczak-Marczak, Monika; Kuna, Piotr; Kupczyk, Maciej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Venom immunotherapy (VIT) is recommended as the first-line treatment for patients allergic to Hymenoptera venom. Aim: To analyze the safety and efficacy of VIT in a real life setting. Material and methods: One hundred and eighty patients undergoing VIT were studied to evaluate the safety, efficacy, incidence and nature of symptoms after field stings and adverse reactions to VIT. Results: Significantly more patients were allergic to wasp than bee venom (146 vs. 34, p < 0.0001). Early and late side effects were more common during the maintenance (48 patients, 26.7%) than during the induction of VIT (32 patients, 17.8%), were more frequent in patients allergic to bees, and were not associated with angiotensin convertase inhibitors (ACEi) or β-adrenergic antagonists use. Systemic reactions were observed in 4 individuals on wasp VIT (2.7%) and in 6 patients allergic to bees (17.65%). The VIT was efficacious as most patients reported no reactions (50%) or reported only mild local reactions (43.75%) to field stings. The decrease in sIgE at completion of VIT correlated with the dose of vaccine received (r = 0.53, p = 0.004). Beekeeping (RR = 29.54, p < 0.0001) and female sex (RR = 1.27, p = 0.033) were associated with a higher risk of venom allergy. Conclusions : Venom immunotherapy is highly efficacious and safe as most of the adverse events during the induction and maintenance phase are mild and local. Side effects of VIT are more common in subjects on bee VIT. Beekeeping and female sex are associated with a higher risk of allergy to Hymenoptera venom.